Development and Characterization of a Hydrogel Containing Curcumin-Loaded Nanoemulsion for Enhanced In Vitro Antibacteria and In Vivo Wound Healing - Thi Thanh Ngoc Le; Thi Kieu Nhi Nguyen; Van Minh Nguyen; Thi Cam Minh Dao; Hoai Bao Chau Nguyen; Cong Thuan Dang; Thi Bao Chi Le; Thi Khanh Linh Nguyen; Phuong Thao Tien Nguyen; Le Hoang Nam Dang; Van Minh Doan; Hoang Nhan Ho (Molecules, 2023)
Curcumin (CUR) is a natural compound extracted from turmeric (Curcuma longa L.) used to cure acne, wound healing, etc. Its disadvantages, such as poor solubility and permeability, limit its efficacy. Nanoemulsion (NE)-based drug delivery systems have gained popularity due to their advantages. This study aimed to optimize a CUR-NE-based gel and evaluate its physicochemical and biological properties. A NE was prepared using the catastrophic phase inversion method and optimized using the Design Expert 12.0 software. The CUR-NE gel was characterized in terms of visual appearance, pH, drug release, antibacterial and wound healing effects. The optimal formulation contained CUR, Capryol 90 (oil), Labrasol:Cremophor RH40 (1:1) (surfactants), propylene glycol (co-surfactant), and water. The NE had a droplet size of 22.87 nm and a polydispersity index of 0.348. The obtained CUR-NE gel had a soft, smooth texture and a pH of 5.34 ± 0.05. The in vitro release of CUR from the NE-based gel was higher than that from a commercial gel with nanosized CUR (21.68 ± 1.25 µg/cm2, 13.62 ± 1.63 µg/cm2 after 10 h, respectively). The CUR-NE gel accelerated in vitro antibacterial and in vivo wound healing activities as compared to other CUR-loaded gels. The CUR-NE gel has potential for transdermal applications.